Sunitinib represses regulatory T cells to overcome immunotolerance in a murine model of hepatocellular cancer. (2nd January 2018) - Liu, Dai; Li, Guangfu; Avella, Diego M.; Kimchi, Eric T.; Kaifi, Jussuf T.; Rubinstein, Mark P.; Camp, E. Ramsay; Rockey, Don C.; Schell, Todd D.; Staveley-O'Carroll, Kevin F.
ABSTRACT: Successful development of immunotherapeutic strategies for hepatocellular cancer (HCC) has been impeded by limited understanding of tumor-induced profound tolerance and lack of a clinically faithful HCC model. Recently, we developed a novel model that recapitulates typical features of human HCC. Using this clinically relevant model, we demonstrate that tumor growth impairs host immunity and causes a profound exhaustion of tumor antigen-specific (TAS) CD8 + T cells. Increase in frequency and suppressive function of regulatory T cells (Tregs) is critically involved in this tumor-induced immune dysfunction. We further demonstrate that sunitinib suppresses Tregs and prevents tumor-induced immune tolerance, allowing TAS immunization to activate endogenous CD8 + T cells. As a result, this combinational strategy delays tumor growth. Importantly, the additional integration of exogenous naïve TAS CD8 + T cells by adoptive cell transfer (ACT) leads to the elimination of the established tumors without recurrence and promotes long-term survival of the treated mice. Mechanistically, sunitinib treatment primes the antitumor immune response by significantly decreasing Treg frequency, reducing TGF-β and IL-10 production by Tregs, and also protecting TAS CD8 + T cells from tumor-induced deletion in the setting of HCC. Taken together, sunitinib quantitatively and qualitatively modifies Tregs to overcome tumor-induced immune deficiency, suggesting the potential of sunitinib as a therapeutic immune activator for HCC control.